Single-cell reporters for pathogen responses to antimicrobial host attacks. (February 2021) - Roche, Béatrice; Bumann, Dirk
Highlights: Reporters reveal exposure of individual pathogen cells to diverse host attacks. Reporters detect pathogen responses but inducing stimuli are difficult to identify. Impact of host attacks on single-cell pathogen fitness can be elucidated. Tools to interrogate mechanisms connecting damage to fitness defects are lacking. Abstract : Host–pathogen interactions are often heterogeneous involving individual encounters between host and pathogen cells with diverse molecular mechanisms, response networks, and diverging outcomes. Single-cell reporters can identify the various types of interactions and participating pathogen subsets, help to unravel underlying molecular mechanism, and determine individual outcomes and their impact on disease progression. In this review, we discuss reporters-based on fluorescent proteins. We present different types of reporters and their experimental advantages and challenges, and describe how different strategies can interrogate exposure to antimicrobial host mechanism, pathogen response, inflicted damage, and impact on pathogen fitness at the single-cell level. We find many gaps in available tools but also exciting avenues to address these issues.